DOES BANK COMPETITION INCREASE OR IMPEDE SMALL BUSINESS INNOVATION? EVIDENCE FROM DEVELOPING COUNTRIES - Duc Nguyen Nguyen (Tạp chí Khoa học Đại học Đà Lạt)
The influence of bank competition on innovation has been examined in the literature, but the evidence has yielded contrasting results and has mainly focused on large or listed enterprises in a single market. This study investigates the relationship between bank competition and innovation by small businesses in less developed markets using 45,669 observations from 51 low-income and lower middle-income countries. The results indicate a positive relationship between bank competition and the likelihood of innovation. The positive association is confirmed for alternative indicators of bank competition and innovation, different econometric techniques, and alternative sample selection criteria. The results provide essential implications for small businesses and policymakers in less developed markets, including ASEAN and various geographical regions around the world.